2022
DOI: 10.1177/20563051221129156
|View full text |Cite
|
Sign up to set email alerts
|

“Dark Participation” Without Representation: A Structural Approach to Journalism’s Social Media Crisis

Abstract: Social media platforms have become an integral part of journalistic work. These tools allow journalists to pursue stronger, more intimate connections with their audiences, to cultivate their own professional identities or “brands,” and to advocate for improved working conditions within their organizations. Yet, social media platforms have also created new risks and challenges for journalists, most notably in the form of dark participation, which refers to negative, selfish or even deeply sinister forms of onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…We know journalists often forgo bringing online harassment, including threats, to the attention of their editors because they assume it is not serious enough to mention (Deavours et al, 2022). Newsroom management has been found to offer no or insufficient support in regard to online hostility and harassment (Holton et al, 2021) and that social media policies regarding how to engage with audiences who are hostile online are vague or lacking entirely, with little to no intervention from superiors (Miller & Nelson, 2022), which puts the onus of dealing with hostility on individual reporters. Bugeja (2023) found that when online harassment is brought to management's attention, "publishers and general managers typically advise reporters to block the trolls and ignore the digital assaults" (p. 80), minimizing the seriousness of the situation and any related mental health effects journalists could be experiencing in response to hostility.…”
Section: Editorial Support In the Newsroommentioning
confidence: 99%
“…We know journalists often forgo bringing online harassment, including threats, to the attention of their editors because they assume it is not serious enough to mention (Deavours et al, 2022). Newsroom management has been found to offer no or insufficient support in regard to online hostility and harassment (Holton et al, 2021) and that social media policies regarding how to engage with audiences who are hostile online are vague or lacking entirely, with little to no intervention from superiors (Miller & Nelson, 2022), which puts the onus of dealing with hostility on individual reporters. Bugeja (2023) found that when online harassment is brought to management's attention, "publishers and general managers typically advise reporters to block the trolls and ignore the digital assaults" (p. 80), minimizing the seriousness of the situation and any related mental health effects journalists could be experiencing in response to hostility.…”
Section: Editorial Support In the Newsroommentioning
confidence: 99%
“…La participación en línea, aunque tiene su lado oscuro (Lutz;Hoffmann, 2017), exige, como fenómeno multidimensional complejo que es, esfuerzo a los usuarios, tanto en las acciones orientadas a la recepción como en las orientadas a la producción (Nelson, 2021) (Nelson, 2021). Las iniciativas de los medios periodísticos para complacer a la audiencia, que pueden ser compatibles con producir un periodismo excelente (Meijer, 2013), se han multiplicado y los medios nativos digitales tienden a cuidar especialmente esta dimensión, sobre todo a través de las plataformas de redes sociales, que se han convertido en parte integral del trabajo periodístico (Miller;Nelson, 2022). El diálogo de los periodistas digitales con las audiencias tiene cada vez más vías y los periodistas consideran una necesidad prioritaria mantener una relación fluida con las audiencias, mientras que los responsables de los medios contemplan la participación principalmente como un canal para fidelizar audiencias y aumentar audiencias (Peña-Fernández et al, 2021).…”
Section: Introductionunclassified
“…In this context, journalism is believed to be moving towards more openness and engaging in the digital era, and data journalism has been considered an innovative form and prominent feature of today’s journalism (Tong, 2022a: 47–60). Data journalism has been regarded not only to be more immersive, objective and accurate than traditional journalism by introducing huge data, digitization and visualization techniques, and computational science into news production, but also to be more interactive and engaging, which affords new opportunities for the audience to engage in the creation, distribution and consumption of news (Boyles and Meyer, 2016; Miller and Nelson, 2022).…”
Section: Introductionmentioning
confidence: 99%